Sports Civic Organizations-Subsidies and the Subsidy Exposure - Szabados, György Norbert; Bácsné Bába, Éva; Fenyves, Veronika; Bács, Zoltán; Dajnoki, Krisztina; Kovács, Sándor (International Journal of Engineering and Management Sciences, 2018)
When we discuss the topic of civic organizations, especially sports profile civic organizations we need to note and comment that issue how these organizational forms are able and capable to accept subsidies. The related data of the Central Statistical Office (KSH) highlight the phenomenon that incomes of the classic civic organizations are mainly composed of state or private source donations. Although there is a really and pretty predictable subsidy system in the field of civic sphere currently, from one hand the distribution of the single subsidy forms considerably vary, on the other hand it result in the considerable amount of available financial resources. The fact whether subsidy forms and subsidy incomes have relationship with the addition alvariables of the organizational operation, such as subsidies provided, employment relationship, and expenditures may acquire special attention at the management of organizational operation together with the planned strategic interventions in the field of the civic sphere.